Preliminary evaluation of an extract of Amaranthus caudatus as a novel nutraceutical: effects on cholesterol and glucose absorption - Mattiello, Alessia; Barbaglio, Gloria; Magnone, Mirko; Scarfì, Sonia; Vernazza, Stefania; Mirata, Serena; Markus, Jan; Letasiova, Silvia; Riva, Danilo; Premoli, Roberto (Frontiers in Nutrition, 2026)
IntroductionThe increasing prevalence of metabolic syndrome has prompted the development of nutraceuticals to support the management of glucose intolerance and dyslipidemia. Amaranthus caudatus is a potential source of bioactive compounds with metabolic relevance.MethodsA novel ingredient derived from Amaranthus caudatus seeds was characterized by untargeted metabolomic analysis and bioinformatic processing. Its effects were evaluated through in vitro enzyme inhibition and intestinal absorption assays, as well as preliminary observations in subjects with glucose intolerance over 3 months.ResultsThe extract significantly inhibited key enzymes involved in carbohydrate metabolism and reduced glucose and cholesterol absorption in a three-dimensional intestinal model, while showing antioxidant activity. Preliminary human observations indicated improvements in HbA1c, post-prandial glucose, BMI, and a trend toward reduced total and LDL cholesterol.DiscussionThese results suggest that Amaranthus caudatus seed extract may represent a promising nutraceutical for supporting glycemic control and lipid metabolism.